Ramblings of a Lowcountry Game Warden : A Memoir - Moïse, Ben McC (Book collections on Project MUSE., 2008)
Ben McC. Moïse served with distinction as a South Carolina game warden for nearly a quarter century, patrolling the coastal woods and waters of the Palmetto State. In this colorful career-spanning memoir, the cigar-chomping, ticket-writing scourge of lowcountry fish-and-game-law violators chronicles grueling stakeouts, complex trials, hair-raising adventures, and daily interactions with a host of outrageous personalities. With a lawman's eye for fine details, a conservationist's nose for the aroma of pluff mud, and a seasoned storyteller's ear for the rhythms of a good southern yarn, Moïse recounts his stout-hearted and steadfast efforts to protect the lowcountry landscape and bring to justice those who would run roughshod over fish and game laws on the Carolina coast. Along the way he paints a vivid portrait of evolving attitudes and changing regulations governing coastal conservation.